Gereja dan Stunting: Integrasi Tanggung-Jawab - Fotarisman Zaluchu (SUNDERMANN: Jurnal Ilmiah Teologi, Pendidikan, Sains, Humaniora dan Kebudayaan, 2023)
Stunting is a serious problem currently faced by Indonesia. About 20 out of 100 children under five years old suffer from stunting. The stunting condition is so severe that it has even occurred since the beginning of life, when a new child is born, characterized by a height and birth weight below the recommended minimum size. The church is an organic entity that should not only convey the truth of God's word, but also provide solutions to the problem of stunting. Jesus' command to the disciples in Mark 6:35-44 to feed the people is the basis for the discussion of this paper, which will open the paradigm of the church's involvement in handling stunting in the future. There are many things that the church can do, directly or indirectly, for pregnant women and mothers of under five children.